1992
DOI: 10.1104/pp.98.2.573
|View full text |Cite
|
Sign up to set email alerts
|

Decrease of Nitrate Reductase Activity in Spinach Leaves during a Light-Dark Transition

Abstract: In leaves of spinach plants (Spinacia oleracea L.) performing CO2 and N03-assimilation, at the time of sudden darkening, which eliminates photosystem I-dependent nitrite reduction, only a minor temporary increase of the leaf nitrite content is observed. Because nitrate reduction does not depend on redox equivalents generated by photosystem I activity, a continuation of nitrate reduction after darkening would result in a large accumulation of nitrite in the leaves within a very short time, which is not observed… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
54
0
5

Year Published

1994
1994
2009
2009

Publication Types

Select...
4
3
2

Relationship

0
9

Authors

Journals

citations
Cited by 123 publications
(63 citation statements)
references
References 32 publications
(34 reference statements)
4
54
0
5
Order By: Relevance
“…In illuminated spinach leaves from plants fertilized with nitrate, extractable NRA was about 10 to 20 pmol NO3-g-' fresh weight h-', compared to a COZ-assimilation rate of 100 to 200 pmol g-' fresh weight h-'. Upon sudden darkening, NRA decreased by 50 to 85%, with a half-time of only 2 to 15 min (Huber et al, 1992a;Huber et al, 1992c;Kaiser et al, 1992;MacKintosh, 1992;Riens and Heldt, 1992;De Cires et al, 1993).…”
Section: Light/dark Modulationmentioning
confidence: 99%
“…In illuminated spinach leaves from plants fertilized with nitrate, extractable NRA was about 10 to 20 pmol NO3-g-' fresh weight h-', compared to a COZ-assimilation rate of 100 to 200 pmol g-' fresh weight h-'. Upon sudden darkening, NRA decreased by 50 to 85%, with a half-time of only 2 to 15 min (Huber et al, 1992a;Huber et al, 1992c;Kaiser et al, 1992;MacKintosh, 1992;Riens and Heldt, 1992;De Cires et al, 1993).…”
Section: Light/dark Modulationmentioning
confidence: 99%
“…Kaiser and Spill (1991) suggested that the cytosolic ATP/AMP levels are the central link between the nitrate reductase activity in the cytosol and photosynthesis in the chloroplasts. On the other hand, Riens and Heldt (1992) who observed a rapid inactivation of the nitrate reductase activity of spinach leaves under sudden darkness suggested that this phenomenon was related to the mechanism used for avoiding the accumulation of toxic nitrite in cells. Such a light effect on the nitrate reductase activity may not be involved in the present study, because sampled leaf tissues were quickly frozen with ice immediately after detachment from growing plants under full sunlight.…”
Section: Discussionmentioning
confidence: 99%
“…Una vez absorbido, para que el nitrato pueda ser asimilado en forma de estructuras orgánicas, tiene que ser reducido a amonio lo cual se produce mediante dos reacciones catalizadas por las enzimas nitrato reductasa y nitrito reductasa (Ingle et al, 1966;Weissman, 1972;Guardiola, García, 1990;Riens, Heldt, 1992).…”
Section: Asimilación Del Nitrógenounclassified
“…Este proceso requiere energía, pudiendo consumir una parte de los electrones originados en la fotosíntesis (Riens, Heldt, 1992;Bungard et al, 1999).…”
Section: Reducción Del Nitratounclassified